Endogenous money and the natural rate of interest: The reemergence of liquidity preference and animal spirits in the post-Keynesian theory of capital markets - Philip Pilkington (Levy Economics Institute of Bard College, 2014)
Since the beginning of the fall of monetarism in the mid-1980s, mainstream macroeconomics has incorporated many of the principles of post-Keynesian endogenous money theory. This paper argues that the most important critical component of post-Keynesian monetary theory today is its rejection of the "natural rate of interest." By examining the hidden assumptions of the loanable funds doctrine as it was modified in light of the idea of a natural rate of interest - specifically, its implicit reliance on an "efficient markets hypothesis" view of capital markets - this paper seeks to show that the mainstream view of capital markets is completely at odds with the world of fundamental uncertainty addressed by post-Keynesian economists, a world in which Keynesian liquidity preference and animal spirits rule the roost. This perspective also allows us to shed new light on the debate that has sprung up around the work of Hyman Minsky, calling into question to what extent he rejected the loanable funds view of financial markets. When Minsky's theories are examined against the backdrop of the natural rate of interest version of the loanable funds theory, it quickly becomes clear that Minsky does not fall into the loanable funds camp.
Keywords: E00; E12; E40; E43; E44; 330; Capital Markets; Financial Economics; Financial Market Theory; Macroeconomics; Monetary Economics; Monetary Theory